2021
DOI: 10.1111/apa.15908
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis is not a marker of bridging vein rupture in infants with alleged abusive head trauma

Abstract: Diagnosis of bridging vein thrombosis in infants has become more common in recent years. Controversy has arisen as to whether the diagnosis of thrombosis can be used as a marker for traumatic bridging vein rupture. Specifically, the radiological diagnosis of thrombosis has been suggested as a marker of abusive head trauma (AHT), the so-called lollipop or tadpole signs on magnetic resonance imaging

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
0
7
0
1
Order By: Relevance
“…[3][4][5][6][7] Therefore, the veins in the subdural part are more fragile than the subarachnoid space. 26 The present study in rat pups showed that spinal anesthesia caused both subdural hematoma and epidural hematoma. Epidural and subdural hematoma occurred following lumbar puncture in cases of cerebral aneurysm, cerebral tumor, and cerebrovascular accidents.…”
Section: Discussionmentioning
confidence: 50%
“…[3][4][5][6][7] Therefore, the veins in the subdural part are more fragile than the subarachnoid space. 26 The present study in rat pups showed that spinal anesthesia caused both subdural hematoma and epidural hematoma. Epidural and subdural hematoma occurred following lumbar puncture in cases of cerebral aneurysm, cerebral tumor, and cerebrovascular accidents.…”
Section: Discussionmentioning
confidence: 50%
“…We agree absolutely with Donaruma et al that “Another point demanding clarification is interpreting venous thrombosis as representative of vascular trauma.” 1 This clarification was the point of our article 2 …”
mentioning
confidence: 86%
“…1 This clarification was the point of our article. 2 Our article is based on data acquired by review of the literature concerning the validity of the hypothesis that thrombosis of bridging veins (BV) is a marker of rupture and abuse; an opinion would not require such a factual basis.…”
Section: Demanding Clarification That Venous Thrombosis Is Representa...mentioning
confidence: 99%
“…18,42,79,85 Zahl et al assert that thrombosis is not a marker of BV rupture in infants with alleged AHT. 86 Rambaud reports BV ruptures from autopsies. 49 In the radiologic study by Krasnokutsky CVST/BV thrombosis from trauma did not correlate with trauma severity.…”
Section: Bv Rupturementioning
confidence: 99%